MENELUSURI MANAJEMEN LEMBAGA PENDIDIKAN ISLAM DALAM MENINGKATKAN MUTU MADRASAH DINIYAH DARUN NAFI’ KECAMATAN BANDUNGAN KABUPATEN SEMARANG - Arif Khoirun Nasikhin (Nusantara Hasana Journal, 2025)
This study aims to analyze the institutional management of Madrasah Diniyah Darun Nafi' in improving the quality of Islamic education, with a focus on planning, organizing, implementing, and supervising. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The results show that planning is carried out in a participatory manner with a pesantren-specific curriculum, but teacher competency development has not been systematically programmed, and facilities and infrastructure are still limited. In terms of organization, the institutional structure is functioning properly, but it is not yet supported by official documents such as job descriptions and SOPs. Learning is carried out according to schedule with an even distribution of teachers and materials that reflect Islamic values. Meanwhile, supervision and evaluation are still conventional, do not use standardized assessment instruments, and community involvement is still limited and not optimally organized. These conditions indicate the need to strengthen data-based management and develop a structured evaluation system and community involvement. This study recommends improvements in the managerial system, both administratively and operationally, to support the quality of Islamic education in madrasah diniyah.